Shawn Gavlick: capstone - Gavlick, Shawn, artist (Colorado State University. Libraries, 2013)
The artist's statement: Photography works different than many other media, in that the photographer edits down to a final image from a wide variety of options. In my own photography I have worked in a manner which I choose what needs to be included in the image crafting a situation from nothing. Starting with a clean slate, decisions of shapes, objects, and tones are combined to create the final images seen here. The work exists without the use of any manipulation analogue or digitally, the constructions are recorded true to life. The camera and artificial lighting factually describe the objects in a studio environment allowing for complete control. This process allows for more decisions by the photographer all while taking away much of the automation that is used in modern photography. The show is crafted by hand, images are captured on film, prints are crafted in the darkroom and even the frames are handmade. Control of the materials is demanded and there is a responsibility of the photographer in the production of the finished pieces as well as the creation of the images. From start to finish the pieces are controlled and crafted by my hands.
Silver Halide
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.